A case of recurrent stroke with underlying adenocarcinoma: Pseudo-cryptogenic stroke - Deepak Goel (Brain Circulation, 2020)
Stroke is the most common neurological disorders leading to early death. Early recognition of underlying mechanisms and etiology of stroke is important to prevent recurrence, mortality and disability. The term cryptogenic stroke or embolic stroke of undetermined sources is used where no etiology could be detected. We are describing this rare case of “recurrent stroke with undetermined etiology” finally proved to have an uncommon underlying etiology.